Anti-K1 (Kell) Antibody Expressed in Maternal Breastmilk: A Case Report of a Neonate with Multiple Intrauterine Transfusions and Postnatal Exposure to Kell Antibody in Maternal Breastmilk - Patrick DeMoss; Mohamed Asfour; Kelly Hersey (Hindawi Limited, 2017)
Hemolytic disease of the fetus and newborn is a common consideration in newborn medicine, especially among the jaundiced. Maternal breastmilk provides numerous benefits to the infant, including nutrition and immunologic factors. Here, we present an infant who received three intrauterine transfusions for anemia secondary to anti-K1 (Kell), anti-C, and anti-e antibodies and whose maternal breastmilk tested positive for anti-Kell antibodies. The infant required another transfusion at 4 weeks of life for anemia. We review the pathophysiology of anti-Kell antibodies, the immunology of breast milk, and the intersection of these two topics.